Valuation considerations of stock based compensation: a case study of semiconductor firms - Engel, Russell; Lyons, Bridget (Journal of Accounting and Finance, 2025)
Equity research analysts and investors remain divided on the treatment of stock-based compensation (SBC) in firm valuation, particularly in discounted cash flow (DCF) and earnings multiples techniques. Many firms and analysts exclude SBC, viewing it as a non-cash expense, while others argue this leads to overvaluation. SBC usage is especially high in the tech sector. This study examines five large semiconductor firms, analyzing SBC levels, its treatment in adjusted earnings, and its impact on share dilution, valuation multiples, and free cash flow calculations. Findings indicate that SBC treatment significantly affects valuation, particularly within the semiconductor industry.
Keywords: Accounting; Actuarial science; Business; Econometrics; Economics; Engineering; Finance; Financial economics; Stock (firearms); Stock options; Valuation (finance); dept.acc

Generalist CEOs and operational efficiency - Chung, Hanyong (Finance research letters, 2025)
Keywords: Accounting; Board of directors; Business; Economics; Firm size; Generalist CEO; Generalist and specialist species; Operational efficiency; dept.acc; peer-reviewed

Improving Student Performance in Introductory Accounting - Raising Minimum Grade Standards is Not the Answer - Phillips, Janet (The Accounting Educators' Journal, 2021)
An ongoing debate continues at universities surrounding whether or not to raise minimum grade standards. Because of an inherent risk that enrollments may decline as a result, it is important to examine whether minimum grade policies are associated with improved student performance. To address this issue, the current study examines the relationship between higher minimum grade requirements in introductory accounting and student grades. The new minimum grade requirement of â€œCâ€ was established beginning with the fall 2015 semester for introductory accounting to strengthen the quality of the program for an AACSB application. The research design included modeling introductory accounting grades over a ten-year period to examine any effect of the increase in the minimum grade on studentsâ€™ grades in the course. The multivariate regression equation considered variables previously found associated with introductory accounting grades (i.e., status as accounting major, grade point average, mathematics preparedness and previous experience taking the course). An additional dichotomous variable was introduced to capture the impact of students on the new program. All students were taught by the same professor, using the same textbook, teaching philosophy and examination format to enhance the comparison. Results suggest average grades in introductory accounting did not improve as expected.
Number: 1
Keywords: dept.acc; peer-reviewed; ⛔ No DOI found

An Examination of the Relationship Between the Funded Status of Defined Benefit Pension Plans and the Financial Condition of Sponsoring Organizations – Public Vs Private Sector - Phillips, Janet F. (Journal of Accounting Ethics and Public Policy, 2022)
Defined benefit pension plans are a bedrock of the U.S. economy providing guaranteed payment streams at pre-established amounts. Results suggest public plans, sponsored by State and Local governments, and private plans, sponsored by public corporations, are unfunded. State plans were found to have the largest pension and unfunded pension liabilities. Examination of relationships between unfunded pension liabilities and fiscal or financial stability of sponsoring organizations suggests unfunded State pension plans are more likely to be sponsored by financially struggling sponsors measured by general obligation bond ratings. Local governments and Corporations with unfunded pension plans are less likely to be struggling financially. Fiscal distress of Local governments was measured by survival analysis. Corporation financial distress was quantified by a model designed to predict bankruptcy. Financially stable organizations failing to fund pension plans, in this case local governments and corporations, suggests a lack of social responsibility.
Keywords: Defined benefit pension plans; dept.acc; financial or fiscal distress; peer-reviewed; social responsibility; unfunded pension liabilities; ⛔ No DOI found

How to Handle Pressure to Act Unethically - Haylon, Lisa S.; Bishop, Carol C.; Boyle, Douglas M.; Hermanson, Dana R. (Management Accounting Quarterly, 2022)
It is likely that accountants will face pressure to act unethically during their careers. We offer 10 practical steps to help financial professionals prepare for and respond to the pressure to act unethically.
Num Pages: 1-9 Place: Montvale, United States
Keywords: Accounting; Business And Economics–Accounting; Business And Economics–Management; Business ethics; Compliance; Conformity; Decision making; Fraud; Management accountants; Personality; Professionals; dept.acc; peer-reviewed; ⛔ No DOI found

A data analytics mindset with Crisp-Dm - O'Hara, Richard; Haylon, Lisa S.; Boyle, Douglas M. (Strategic Finance, 2023)
According to a 2020 survey of 600 senior executives conducted by Harvard Business Review, 55% of organizations agreed that data analytics for decision making is extremely important and 92% asserted data analytics for decision making will be even more important in two years (bit.ly/3PBRENs). Organizations that strategically deploy tools across their finance and accounting functions have an opportunity to better structure manual processes into more stable, accurate, repeatable, and readily auditable procedures (see Gregory Kogan, Nathan Myers, Daniel J. Gaydon, and Douglas M. Boyle, "Advancing Digital Transformation," Strategic Finance, December 2021, bit.ly/3V45v0h). [...]financial decision makers are increasingly expected to engage data analytics to enhance decision making and create more efficient processes. Deployment/communication It's very important to assign responsibilities to team members (e.g., business analysts establish requirements, IT specialists gather required data, and data scientists develop and test advanced modeling techniques) with the requisite skills that vary among the phases. [...]unstructured data is data that has no uniform structure and typically isn't text-based, for example, image or sound files.
Num Pages: 38-45 Place: Montvale, United States
Keywords: Business And Economics–Accounting; Data analysis; Data mining; Decision making; Decision support systems; Enterprise resource planning; Management accounting; dept.acc; peer-reviewed; ⛔ No DOI found

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Number: 2
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found